Perlindungan Hukum Bagi Masyarakat Atas Penggunaan Tanahnya Untuk Proyek Jalan Tol Demi Kepentingan Umum - Sobur, Muhammad; Gunawan; Sari, Rizkita Kurnia (Universitas Muhammadiyah Kotabumi, 2025)
The construction of toll roads often comes into contact with the community, because the land used in the construction often involves community land, legal protection efforts for the community whose land is used for the construction of toll roads for public interest are very important considering that community losses are often not paid. Like the case of the Bajaj Bajuri Mat Solar comedy soap opera actor who has not received compensation for the construction of the Cinere-Serpong Toll project. For the public interest, the community is legally protected from the use of their land for toll road projects. In addition to knowing the community's efforts to obtain compensation in accordance with legal provisions reviewed from Law Number 2 of 2012 concerning Land Acquisition for Public Interest, this is intended to ensure legal protection for the community regarding the use of their land for toll road projects. The research methodology used is the normative legal approach (normative legal research method). By examining the laws and regulations and library sources, a normative legal research approach was carried out. This study focuses on library research to examine the legal materials used, both primary, secondary, and tertiary. The results of the study indicate that there is an imbalance between the legal provisions stipulated in the law and the reality of its application in the field. These factors include the lack of information in the community regarding the legal protection provided or the lack of public knowledge about community rights. Although some people are not satisfied with the compensation they receive, they can file a lawsuit with the local district court within 14 days of the minutes of the deliberation being signed to obtain the value and form of compensation. The government has ensured that the community can obtain their rights by following the deliberation path with the land institution with the recipient party. The lack of knowledge of the lower class community to obtain legal assistance and the large number of people who do not know their legal rights regarding land ownership are obstacles in defending the community whose land is used for toll road construction. This often causes them to be unable to fight for their rights when their land is used for public interest. .